Comercialización y rentabilidad de los microcréditos otorgados por la Cooperativa Cacpeco y su relación con la economía del cantón La Maná, año 2010 - Castillo Granja, María Fernanda (2013)
The economic changing factors of the country affect the development of La Maná Canton, because they have a very important role in the financial services of the public and private entities that serve as strong support for investing in feasible alternatives to strengthen growth and micro business market leadership. The main purpose of this research was to study the marketing and profitability of micro credits granted by “CACPECO” Cooperative whose current contribution is valuable and should continue encouraging partners, providing a quality service that can satisfy the needs of their own welfare and community....